2012
DOI: 10.5812/ijhrba.4968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methadone Maintenance Therapyon Anthropometric Indices in Opioid Dependent Patients

Abstract: BackgroundOpium abuse significantly affects the nutritional status of users and frequently leads to undernourishment. Methadone maintenance therapy has been used as one of the possible ways to prevent of infection diseases such as HIV and hepatitis B and C and improve the quality of life in opioid-dependent patients.ObjectivesThe aim of this study was to assess the anthropometric and socio-demographic characteristics of opium addicted persons before and after 8 weeks of methadone maintenance therapy (MMT).Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
(17 reference statements)
2
20
1
Order By: Relevance
“…However, the proportion of those in the obese category doubled. As shown by Montazerifar et al ( 3 ), the percentages of underweight, overweight and obese patients were 27.3%, 18.2% and 3.6%, respectively before methadone treatment, and 12.7%, 18.2% and 7.2% at the end of the 8 weeks. A subsequent US study of 69 methadone patients by Fenn et al ( 4 ) also found a significant increase in BMI from admission to follow up.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, the proportion of those in the obese category doubled. As shown by Montazerifar et al ( 3 ), the percentages of underweight, overweight and obese patients were 27.3%, 18.2% and 3.6%, respectively before methadone treatment, and 12.7%, 18.2% and 7.2% at the end of the 8 weeks. A subsequent US study of 69 methadone patients by Fenn et al ( 4 ) also found a significant increase in BMI from admission to follow up.…”
Section: Introductionmentioning
confidence: 72%
“…Okruhlica and Slezakova ( 5 ) hypothesized that the weight gain of their patients in opiate substitution treatment is most probably a consequence of the changes in their lifestyle and not the result of direct adverse pharmacological effect of methadone medication. The findings by Okruhlica and Slezakova ( 5 ), if replicated, are of crucial medical importance because they suggest that the rapid weight increase such as the twofold increase of patients within the obese category observed by Montazerifar et al ( 3 ) within the time span as short as only 8 weeks does not continue beyond the first or the second year of methadone treatment and is perhaps more related to changes in lifestyle than to pharmacological properties of methadone.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…MetS represents a complex pathophysiological condition that may develop in OUD patients [54][55][56][57] even independent of MAT, from increased caloric intake, decreased energy expenditure owing to reduced physical activity or a combination of both 8,21 . This assertion is however undermined by: (1) preponderance of studies reporting low body weight in short half-life opioid (e.g., heroin) abusers who are not on MAT agonist therapy [58][59][60][61] even in the face of glucoregulatory abnormalities [62][63][64] ; and (2) excessive BWG consistently noted in OUD patients following the initiation of methadone [65][66][67][68][69][70][71] and to a lesser degree buprenorphine 6,7,72 treatment. Nonetheless, the debate about the issue is still ongoing 73 with a number of reports on the opposite directionality of the metabolic responses 74,75 , including hemoglobin A1C level decreases in buprenorphine-maintained NIDDM patients 76 in conjunction with heightened insulin sensitivity in methadone-treated OUD patients 77 as well as hypoglycemia in patients receiving chronic analgesia with methadone 78 .…”
mentioning
confidence: 99%
“…During recent years, methadone/buprenorphine maintenance therapy (MMT/BMT) has been one of the effective methods in controlling substance abuse and risky behaviors in Iran (1,2). However, one of the major challenges of this therapeutic approach is treatment retention rate (3).…”
mentioning
confidence: 99%